Tax and growth in a developing country: The case of Brazil - Adolfo Sachsida; Mário Jorge Cardoso de Mendonça (Institute for Applied Economic Research (ipea), 2016)
This paper uses Brazilian quarterly data, from the period January/2002 to June/2015, to estimate the impact of taxes over gross domestic product (GDP) per capita. The econometric results show a negative and statistically significant impact of the overall tax burden over per capita GDP. In average, an increase of 1 percent in the overall tax burden decreases GDP per capita by 0.3 percent. This result is very similar in magnitude with those presented by Heady et al. (2011). Furthermore, additional econometric results pointed out that a revenue neutral fiscal policy which changes the tax structure toward consumption taxes and personal income taxes would improve economic growth. Besides that, we strongly recommend against both taxes over the capital stock (mainly the recurrent ones) and the corporate income taxes.
Keywords: E62; E69; H20; 330; tax; economic growth; fiscal policy prescription